Optimal Vetiver Hedgerow Spacing for Mitigating Sediment and Runoff Erosion on Steep Slopes in Malawi - Judith Francesco Kamoto; Chisomo Mussa; Kondwani Banda; Nicholas Ozor (Journal of Agricultural Extension, 2023)
This study assessed the optimum vetiver hedgerow spacing capable of reducing sediment and runoff erosion on a 17% slope. Three treatments were used: 2-meter vetiver hedgerow spacing, 4-meter vetiver hedgerow spacing, and a control plot without vetiver. Erosion pins were strategically placed on the plots and measured periodically over a period of 6 months, accompanied by daily rainfall measurements. The findings revealed the effectiveness of vetiver hedgerows in reducing sediment erosion and runoff from the plots. Notably, the 2-meter vetiver hedgerow spacing proved more efficient in reducing erosion and minimizing soil accumulation within the plot, with an average change in erosional pin height of 1.2 cm, whereas the 4-meter hedgerow spacing exhibited higher erosion rates at 2 cm, which was statistically significant. These results underscore the importance of optimizing vetiver hedgerow spacing to effectively combat soil erosion and runoff on steep slopes.